Simulasi aliran sungai ... [et al.] / [mikrofilem] - 199211 Zurifah Zulkifli; Yap, Shy Hann; Tuan Khusairry Tuan Abdul Manaf; Rohmen Tasarib; Sharruddin Long (Skudai : Universiti Teknologi Malaysia, 1999)
Kertas projek (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 1999